Clinical analysis of multiple flaps in repairing pressure injuries - Wu, Huwen; Deng, Hanbin; Yao, Jiangling; Yang, Jian; Wang, Rong; Zhang, Peishen; Zhou, Han; Cheng, Shaowen (Frontiers in Surgery, 2025)
BackgroundPressure injuries exhibit high prevalence and are cost-consuming in clinical treatment, and flaps are the most appropriate way for their repair, especially stage III and IV. This study was conducted to investigate the repair effects of different types of flaps and their precautions.MethodsThis study retrospectively analyzed the clinical data of 33 patients with stage III and IV pressure injuries who were hospitalized in our department from April 2021 to December 2023. Data subjected to analysis included the location and size of pressure injuries, treatment, postoperative flap survival, complications, and wound healing after 6 months of follow-up.ResultsOf the 33 patients involved (1 case in stage III and 32 in stage IV), there were 23 cases of sacral pressure injuries, 5 cases of ischial area, 3 cases of hip, 2 cases of back, 19 cases of fascia flaps, 5 cases of musculocutaneous flaps, 9 cases of perforator flaps, 31 cases of postoperative flaps survival, as well as 2 cases of wound healing after debridement and dressing change or re-transplantation of flaps. Furthermore, 4 cases developed complications such as incisal margin necrosis, fat liquefaction, and subcutaneous hematoma, which healed after further debridement and dressing change.ConclusionPressure injuries of different locations, stages, and sizes should be repaired individually with different types of flaps, with emphasis required for perioperative management, as well as postoperative nursing and treatment.